Aprender a cuidar cuidando (2004)
ABSTRACT: This article deals with a ethical reflection related to nursing care experience and about teaching. Aspects of the ethical foundations are analyzed in relation with the conduct leading to the creation of knowledge in order to be able to identify the moments and circumstances to preserve the ethical principles, moral values (virtues) and the internal goodness or the nursing profession: caring with quality.